"The Way All Foster Care Should Be": The Experience of Therapeutic Foster Carers in the Victorian Circle Program. (16th December 2014) - Frederico, Margarita; Long, Maureen; McNamara, Patricia; McPherson, Lynne
Abstract : Central to the success of therapeutic foster care (TFC) is the quality and stability of the relationship between the child and carer. This key relationship may, from a therapeutic perspective, facilitate healing by addressing the impact of complex developmental trauma experienced by the child who has been placed in care. Stability of the carer–child relationship is critical in this context. Therapeutic carers have been shown to be significantly more likely to remain in the role of carer than their counterparts in mainstream foster care. The research reported on in this paper draws upon findings from an evaluation of a TFC programme and gives voice to the Circle Carers, presenting the components of TFC which are important to them. The paper commences with the story of Ruby in TFC as told by a carer. The focus then becomes a detailed exploration of the experience of carers and their capacity to care. Implications for practice are identified.